2022
DOI: 10.3390/pr10071277
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Layered Sol–Gel Spin-Coated CuO Nanofilm Characteristic Enhancement by Sn Doping Concentration

Abstract: CuO films, with their many features, attract special attention for applications in various optoelectronics. In their pristine form, CuO films suffer from low conductivity, which limits their application. Modification, especially by doping, is thus needed. The effects of tin (Sn) doping on the structure, morphology, and optical and, more importantly, electrical properties of multi-layered copper oxide (CuO) films deposited onto tin-doped indium oxide (ITO)/glass substrates by sol–gel spin coating are examined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The substitutional doping of Cu 2+ by Sn 4+ into the CuO crystal lattice generated two holes whereby the Sn 4+ dopants gained two electrons resulting in enhancing the p‐type nature of the composite. [ 21 ] In another study, Sn‐doping was observed to increase the number of electron transfers rates owing to the formation of electron clusters around oxygen atoms connected to Sn impurities as compared to undoped V 2 O 5 . [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…The substitutional doping of Cu 2+ by Sn 4+ into the CuO crystal lattice generated two holes whereby the Sn 4+ dopants gained two electrons resulting in enhancing the p‐type nature of the composite. [ 21 ] In another study, Sn‐doping was observed to increase the number of electron transfers rates owing to the formation of electron clusters around oxygen atoms connected to Sn impurities as compared to undoped V 2 O 5 . [ 22 ]…”
Section: Introductionmentioning
confidence: 99%